Performance analysis of the Next Eleven countries regarding climate change for the selected years - Nuray Tezcan (Journal of Capital Markets Studies (JCMS), 2024)
Purpose - In the Next Eleven (N-11) countries, which are considered emerging investment markets, energy consumption is increasing in parallel with the growing economy. This situation negatively affects global warming and climate change, which are the biggest environmental problems of today. From this point of view, the purpose of the study is to determine the performance of the N-11 countries in terms of energy use and climate change for the period between 2010 and 2022 based on the indicators of Sustainable Development Goal (SDG) 7 and SDG 13 to be reached until 2030. Design/methodology/approach - Grey relational analysis (GRA), one of the multi-criteria decision-making techniques, was used to assess the performance of the N-11 countries in the study. Additionally, the entropy method was employed in determining weights needed in GRA. The indicators were obtained from the World Development Indicators database, World Bank. Performance analyses were conducted for the years 2010, 2015 and 2022, respectively. Findings - According to the results obtained, it has been found that Bangladesh, the Philippines and Egypt have the three highest scores, while Mexico, Indonesia and Iran have the three lowest scores. In 2022, Nigeria is placed instead of Mexico in this group. It is observed that the performance scores of the countries have either remained the same or increased slightly over the years. This indicates that it is difficult to reach the 2030 targets. Originality/value - This study is the first attempt to measure the performance of N-11 countries on climate change using multi-criteria decision-making. In this study, the performance scores obtained for the selected years were compared. Thus, it is observed whether there is an improvement in the performance scores of the countries during the analysis period.
Keywords: 330; Climate change; Energy use; Grey relational analysis; The Next Eleven countries